Calcific uraemic arteriolopathy (calciphylaxis): data from a large nationwide registry. Issue 1 (29th January 2016) - Brandenburg, Vincent M.; Kramann, Rafael; Rothe, Hansjörg; Kaesler, Nadine; Korbiel, Joanna; Specht, Paula; Schmitz, Sophia; Krüger, Thilo; Floege, Jürgen; Ketteler, Markus
Abstract : Background. Calcific uraemic arteriolopathy (CUA, calciphylaxis) is a rare disease predominantly in dialysis patients and associated with high mortality. Painful skin ulcerations and calcification of cutaneous arterioles characterize calciphylaxis. Methods. We established an observational, Internet-based registry allowing online notification for all German CUA cases. The registry recorded data about patient characteristics, biochemistry and therapies. Blood samples were stored in a central biobank. Results. Between 2006 and 2015, 253 CUA patients were recorded: median age 70 [interquartile range (IQR) 61–76] years, 60% females and 86% ( n = 207) dialysis patients, translating into an estimated annual incidence rate of 0.04% in German dialysis patients. Fifty-two per cent received vitamin K antagonists (VKAs) prior to CUA. Skin lesions were localized in 71% on the legs or gluteal region. In dialysis CUA patients median total serum calcium was 2.20 (IQR 2.06–2.37) mmol/L, phosphorus 1.67 (IQR 1.35–2.03) mmol/L, intact parathyroid hormone 147 (IQR 72–276) pg/mL and fetuin-A 0.21 (IQR 0.16–0.26) g/L (normal range 0.35–0.95). Median sclerostin, osteoprotegerin, TRAP5b, bone-specific alkaline phosphatase and c-terminal FGF23 levels were all elevated. The most frequently recorded therapeutic procedures in dialysis CUA patients were as follows: wound debridement (29% of cases), stopping VKA (25%), lowering calcium supply (24%), sodium thiosulphate (22%), application of vitamin K (18%), increase of dialysis duration/frequency (17%) and stoping active vitamin D (16%). Conclusions. Approximately 50% of CUA patients used VKA. Our data suggest that uncontrolled hyperparathyroidism is not the key determinant of calciphylaxis. Therapeutic strategies were heterogeneous. The experience of the German registry will help substantially to initiate a large-scale multinational CUA registry.